Penyuluhan Penanganan Kegawat daruratan Rumah Tangga Di Puskesmas Anak Air Padang - Malinda Meinapuri (Jurnal Pengabdian Warta Andalas, 2016)
Background : In a complex -paced life in modern times it is quite possible emergencies occur in the household environment . Along with the times , the flow of life in the household is becoming increasingly complex , in terms of number of members , the more diverse activities , as well as equipment used to support the passage of life . This can lead to various kinds of accidents in the home , including some circumstances that require immediate relief are classified into a state of emergency , some of choking , burns in children and fever in children . Method : Counseling will be held 1 time meeting ± 2 hours , which cover topics simple handling emergencies Overcoming household burns in children , Fever in children and choking . Extension activities will be preceded by asking cadres and mother - mother Posyandu Charge Sheet kuosioner Mini ( pre -test ) . As well as discussions continued with counseling . At the end of event , cadres and mother - mother Posyandu Requested Back kuosioner Mini Fill the ( post-test ). Result : Extension activities held on Wednesday September 3 , 2014. This event was attended by the extension 27 health cadres who are working in the region of Anak Air Health Center Padang. Material presented on handling emergencies in the household , which on this occasion focused on the handling of fever , burns and choking in children . This material was presented by dr . Malinda Meinapuri , Msi.Med . Furthermore, given the additional material submitted by dr . Nita Afriani , M.Biomed with the topic Breast Self Examination (SADARI) . Conclusion : There was an increased knowledge of health cadres who are working in the region of Anak Air Health Center Padang regarding the handling of emergencies in the household , which on this occasion focused on the treatment of fever , burns and choking in children . There was an increased knowledge of health cadres could be assessed objectively from the increased value kuosioner post-test compared to the pre-test value kuosioner .